Pengaruh Mata Kuliah Kewirausahaan Terhadap Minat Mahasiswa Berwirausaha Menggunakan E-commerce - Sihombing, Samei Johana; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This study aims to determine the effect of entrepreneurship courses on students' interest in entrepreneurship in Economics Education students at Ganesha University of Education. This study uses an inferential approach and the type of data is quantitative. Data collection using a questionnaire. The sample used was 77 students from class 2019. The sampling technique used saturated sampling. Simple regression data analysis technique, classic assumption test, t test hypothesis test and test the coefficient of determination. The results showed that the Entrepreneurship Course had a positive and significant effect on Student Entrepreneurship Interests. This can be seen from the results of a simple regression analysis, the value of the X variable is 0.558, meaning that the increasing X variable will result in an increase in Y variable. The result of the t test is a significance value of 0.000 which is less than 0.05, which means that H0 is accepted and H1 is rejected. The test results for the coefficient of determination R2 of 0.496 means that the influence of Entrepreneurship Course (X) on Interest in Entrepreneurship (Y) is 49.6% while the rest is influenced by other variables.